2023
DOI: 10.47582/jompac.1256573
|View full text |Cite
|
Sign up to set email alerts
|

Akut koroner sendromda akut stent trombozunun ve hastane içi mortalitenin yeni bir inflamasyon göstergesi: çoklu inflamasyon indeksi

Abstract: Aim: The inflammatory milieu plays a triggering role in the development of acute stent thrombosis (ST), which occurs as a catastrophic complication following percutaneous coronary intervention (PCI) in patients with acute coronary syndrome (ACS). This study aimed to investigate the prognostic role of multi-inflammatory index (MII), a powerful new marker of inflammation, in predicting of high SYNTAX score, acute ST and in-hospital mortality in patients with ACS undergoing PCI. Material and Method: This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The SIRI was found to be an independent predictor of LVAR and showed superior diagnostic performance compared to the SII index. Previous studies demonstrated that increased SII index and SIRI were important predictors of cardiovascular events [12][13][14]. Increased SII index and SIRI were related to increased risk of LVAR in patients experiencing STEMI for the first time.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The SIRI was found to be an independent predictor of LVAR and showed superior diagnostic performance compared to the SII index. Previous studies demonstrated that increased SII index and SIRI were important predictors of cardiovascular events [12][13][14]. Increased SII index and SIRI were related to increased risk of LVAR in patients experiencing STEMI for the first time.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, given the potential role of increased IIR in the development of LVAR after acute MI, we hypothesized that there might be an association between leukocyte-based inflammatory indices and the circadian clock. Among these indices, we evaluated the systemic immune inflammation (SII) index and systemic inflammation response index (SIRI), which have not yet been investigated in the context of LVAR but are claimed to have better prognostic roles in predicting cardiovascular events including acute MI [12][13][14]. The SII index, which is an indicator of inflammatory status, is calculated by platelet count × neutrophil count/lymphocyte count [15], while the SIRI, which is an indicator of the balance between the inflammatory response and immune status, is calculated by neutrophil count × monocyte count/lymphocyte count [16].…”
Section: W H a T ' S N E W ?mentioning
confidence: 99%